Dorchester Abbey, Oxfordshire : the archaeology and architecture of a cathedral, monastery and parish church - Rodwell, Warwick (Oxbow Books, 2009)
In this study on the origins, history and architecture of Dorchester Abbey, Rodwell assembles material from observations during repair and conservation, as well as the unexpected discovery of previously unstudied and unpublished topographical and architectural material, housed in several archives.